(untitled) (Archives of Criminology, 2008)
The author of the article, a member of Faculty of Law herself, begins by presenting the two absolute theories of punishment: the one claiming that punishment is necessary, and the opposite theory calling for no punishments at all. There are other theories mentioned as well, such as those created by social scientists who brought up the questions regarding the actual effects of imprisonment. The author then presents the main concept of the article: prisons are institutions created in order to inflict pain and suffering on human beings, which is ethically unacceptable. The author argues that the large numbers of prisoners are hampering the message in cases where the country goes to war to create freedom elsewhere. In her opinion, the low prison rates within welfare states might be seen as arguments for such states, in contrast to those that give free reign to market liberalism. Moreover, it seems to be clear that any increases in the prison population can be used as a warning signal against political developments.